2016
DOI: 10.1016/j.atherosclerosis.2016.08.046
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial-mesenchymal transition in atherosclerotic lesion calcification

Abstract: Background and aims Endothelial-mesenchymal transitions (EndMTs) in endothelial cells (ECs) contribute to vascular disease. Methods We used ApoE−/− mice fed a high-fat/high-cholesterol diet. Results We reported evidence of EndMT in atherosclerotic lesions contributing to calcification. Stem cell and mesenchymal markers, including sex-determining region Y-box 2 (Sox2), were upregulated in aortic ECs of fat-fed ApoE−/− mice. Limiting Sox2 decreased marker expression and calcification in ApoE−/− aortas. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 27 publications
3
57
0
1
Order By: Relevance
“…Previous studies have shown that ECs with mesenchymal and stem cell-like characteristics contribute to cerebral cavernous malformation, atherosclerosis, and the human genetic disorder fibrodysplasia ossificans progressiva (14,18,34). Moreover, ECs undergoing mesenchymal differentiation have been traced in studies of vascular calcification, where ECs gain multipotency and contribute osteoprogenitors to the calcifying process (17,22,35,36). Here, we show the emergence of mesenchymal stem cell markers in the endothelium of cerebral AVMs, which indicate a change in the endothelial fate through EndMTs.…”
Section: Discussionsupporting
confidence: 57%
“…Previous studies have shown that ECs with mesenchymal and stem cell-like characteristics contribute to cerebral cavernous malformation, atherosclerosis, and the human genetic disorder fibrodysplasia ossificans progressiva (14,18,34). Moreover, ECs undergoing mesenchymal differentiation have been traced in studies of vascular calcification, where ECs gain multipotency and contribute osteoprogenitors to the calcifying process (17,22,35,36). Here, we show the emergence of mesenchymal stem cell markers in the endothelium of cerebral AVMs, which indicate a change in the endothelial fate through EndMTs.…”
Section: Discussionsupporting
confidence: 57%
“…In a recent study, based on ex vivo immunolabeling of aortic tissues, cells co‐expressing endothelial and mesenchymal markers were identified in the ApoE ‐deficient atherosclerotic plaques (Boström et al, ). Moreover, the aortic ECs isolated from high‐fat fed mice displayed a strong induction of mesenchymal and osteogenic markers, which correlated with higher expression of several BMP receptors and ligands.…”
Section: Endmt In Cardiovascular Disordersmentioning
confidence: 99%
“…5,6 In the vasculature, instead of osteoblasts driving calcification, vascular smooth muscle cells (VSMCs) undergoing differentiation to an osteogenic phenotype are thought to be a major calcifying type, [7][8][9] although not exclusively so. 10,11 In response to hyperphosphatemia and the presence of other stimulants, VSMCs can enter an osteoblast-like differentiation program that may involve a program of VSMC dedifferentiation before osteogenic redifferentiation or a more direct form of transdifferentiation. [11][12][13][14] VSMCs in culture and in calcifying atherosclerotic plaques can express bone-related proteins, such as bone sialoprotein (BSP), osteopontin (OPN), osteocalcin (OCN), collagen I and II, as well as osteoblastic differentiation factors, such as bone morphogenetic protein 2.…”
mentioning
confidence: 99%
“…10,11 In response to hyperphosphatemia and the presence of other stimulants, VSMCs can enter an osteoblast-like differentiation program that may involve a program of VSMC dedifferentiation before osteogenic redifferentiation or a more direct form of transdifferentiation. [11][12][13][14] VSMCs in culture and in calcifying atherosclerotic plaques can express bone-related proteins, such as bone sialoprotein (BSP), osteopontin (OPN), osteocalcin (OCN), collagen I and II, as well as osteoblastic differentiation factors, such as bone morphogenetic protein 2. 12,[15][16][17] The exact mechanisms driving differentiation are unknown, but may arise because of loss of mineralization inhibitors, such as matrix Gla protein (MGP) or OPN.…”
mentioning
confidence: 99%